T. V. Hrosevych. Features of the novel thinking. - T. V. Hrosevych (Philological Treatises, 2020)
The article is devoted to the study of the specifics of the novel thinking as a literary category. Based on the analysis of the existing theoretical and literary thought on the outlined problem, the definition of the novel thinking is formulated, its main features are selected, and main differences from other types of artistic thinking as well as the relationship with the genre of the novel as the most vivid representative of the romance consciousness are clarified. The author has come to the conclusion that romance thinking and the genre of the novel are genetically and typologically close concepts , interconnected, but not identical. The novel is a constant content-formal category, but romance thinking is dynamic, cognitive, and psychic one. Only the novel model of artistic consciousness is able to reveal the image throughout the breadth of the objective world and throughout the depth of penetration into the subjective world, that is, to portray a person as a subject and an object at the same time. Novel thinking is also analysed in the aspect of creative activity of the artist and is treated as a system of artistic techniques of the novelist.